KEEFEKTIFAN PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS AUDIO VISUAL DALAM MENYUSUN TEKS PUISI SISWA KELAS VII SMP NEGERI I TINAMBUNG - Abdul Muttalib (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2015)
The research is a quasi experiment research with pretest-posttest control design. The population of the research was 94 students who divided into five classes. Cluster sampling technique was used to determine the sample of 36 students who consisted of the control and the experiment classes; each class consisted of 18 students. The instrument of the research was essay test. The data of the research was analyzed by utilizing descriptive statistic and inferential statistic analysis. The results of the research reveal that (1) the poetry writing ability of class VII students at SMP Negeri 1 Tinambung before utilizing audio visual learning media is categorized as unsatisfactory based on the mean score obtain in pre test at the control class by 2.05 with 44.44%. While the mean score of the experiment class is 2.00 with 61.11% (2) the poetry writing ability of class VII students at SMP Negeri I Tinambung after utilizing audio visual learning media on the experiment class is in good category based on the result of post-test which indicated that the mean score is 2,81 with 38.89% (3) the effectiness of utilizing audio visual learning media in writing poetry ability based on the result of hypothesis test showed that t count (5.445) > t table (2.04), in another words, HI is accepted or utilization of audio visual learning media is effective in learning poetry writing of class VII students at SMP Negeri I Tinambung.